Program Tahfidz al-Qur’an sebagai Upaya Pengembangan Karakter Religius dalam Pendidikan Islam: The Tahfidz al-Qur’an Program as an Approach to Developing Religious Character in Islamic Education - Izza Faridah; Anis Sukmawati (Educan, 2026)
The moral dilemmas of the younger generation are increasingly complex, making religious character education urgently needed. Routine Quran memorization activities, which emphasize not only memorization but also the development of discipline, responsibility, honesty, and spirituality in students, are one way schools strive to instill religious values. Studying this program is crucial to understanding its implementation and impact. This article aims to discuss the implementation of routine Quran memorization activities at the UPT SMPN 2 Gresik, and how these activities improve students' religious character through memorization activities. The method used in this article is descriptive qualitative, collecting data through documentation, interviews, and observations. The results show that the implementation of routine Quran memorization activities at the UPT SMPN 2 Gresik has succeeded in becoming an effective medium in improving students' religious character. Despite obstacles, the success of this program demonstrates that with good planning, teacher guidance, parental support, and student awareness, Quran memorization can have a real impact on developing a generation that is religious, disciplined, responsible, honest, and has noble character. This research is expected to assist in the development of Islamic religious education programs in schools, particularly in enhancing religious character development through memorization activities. Furthermore, these findings can be used as a guide for educators, educational institutions, and parents to create more sustainable and effective religious education.